REASONING OF UNETHICAL BEHAVIORAL ISSUE TOWARD ETHICAL DECISION MAKING OF THE OFFENDER IN GIDEON MULA GABE LTD. - Gabe, Gideon Mula; Wisesa, Anggara (Journal of Business and Management, 2018)
Abstract. Ethics become one of the most important thing when we are running the business. The reason is because by doing business ethically we will gain trust. Those who done unethical issue will decrease other trustworthiness to them self or even worst will not have any trustworthiness. This mistrust issue already experienced by Gideon Mula Gabe Ltd. because of the indication corruption phenomenon that happened twice with different management team. By conduct this research, it will make reduction the mistrust of the shareholders. This research used James Rest ethical decision making 4 component models as the conceptual framework, Kohlberg theory of cognitive moral development as the parameter of the ethical decision making, and example of the unethical behavior which state in Ferrell, Fraedrich and Ferrell’s book. This research used phenomenology as the research method in order to understanding the reason of the phenomenon. The researcher found that there are 3 unethical behavior that have been done that related and created suspicious cash activity in audited report: financial misconduct, financial statement fraud, and corruption. The researcher also found that one of the offender that make this phenomenon happened in the fourth stage of cognitive moral development. Keywords:  Cognitive Moral Development, Ethical Decision Making, Phenomenology,  Unethical Behavioral.